Physiotherapy in a whiplash injury: a case report - C. Van Eck (AOSIS, 2008)
Study Design: Case ReportObjectives: To describe physiotherapy intervention in an individual with asuspected whiplash injury.Background: The patient was a 29-year old male with complaints of neckpain and tightness following a motor vehicle accident. Methods and Measures: The focus of the case study is physiotherapyassessment and intervention in a stage II whiplash injury. Results: Following intervention, positive changes occurred in outcome measures such as pain, work status and activities of daily living. Conclusion: Physiotherapy intervention is successful in addressing whiplash associated disorders.